Students’ sense-making as a condition of effective development of personality and motivation during english lessons - Анна Павловна Жданько (Rossijskij psihologičeskij žurnal., 2015)
The author of the article proceeds from the assumption that students’ sensemaking during English lessons is a powerful tool of development of motivation and personality. In this paper we prove that a driving force of sense-making is an exchange of values between teacher and students. The article represents the essence of mechanisms of impact on students’ sense sphere. The procedure of coding of sense sphere that causes certain model of behavior is shown. The first step is finding of extra motives. The second step is a choice of verbal and visual image for establishing sense-bearing links. Also the article underlines the importance of English lessons’ integration into major subjects for increasing meaningfulness of both subjects and appearing of new senses. In that case we deal with interconnection of personal senses and the content of education. Due to the above mentioned fact the content of education is a thing that causes students’ development and academic progress. The article describes methods, which were used for sense-making activization. Among these methods are heuristic conceptual foresight, analytical method, brainstorming. Method of heuristic conceptual foresight allows predict some events by means of analyses of the past and present experience. Analytical method allows to find out the interconnection between the object and factors influencing this object. Brainstorming allows to get a big amount of productive ideas. The article describes psychological peculiarities of students’ age group that contributes to achieving of the aim of the research. In this paper we prove a significant advantage of the sense-making activity for the development of students’ personality.